An experimental study on the effect of a rock-bed heating system on the microclimate and the crop development under canarian greenhouse. (December 2018) - Bazgaou, A.; Fatnassi, H.; Bouhroud, R.; Gourdo, L.; Ezzaeri, K.; Tiskatine, R.; Demrati, H.; Wifaya, A.; Bekkaoui, A.; Aharoune, A.; Bouirden, L.
Highlights: A heating system using solar thermal energy in the greenhouse was evaluated. This system stores solar thermal energy during the daytime and supplies it for heating at night. The system improves the greenhouse microclimate, T increase of 2.6 °C and reduces RH of 10%. This system is capable of improving the yield by 29% and the quality of agricultural production. Abstract: The use of thermal solar energy for heating greenhouse in winter period, where climatic conditions are unfavorable for the plant, is an important issue. In this paper, the performance of a rock-bed heating system is analyzed and discussed in a conventional Canarian type greenhouse in Morocco. An experimental comparative study is conducted in two East-West orientated greenhouses for solving the problem of conventional greenhouses that are facing overheating problems during the day and excessive cold at night, and improving the quality and quantity of agricultural production. The geometry, building materials and date of planting are identical for studying the impact of the heating system on the temperature and humidity inside greenhouse, as well as their influence on the crop development. Results show that the temperature at night inside the greenhouse equipped with the rock-bed exceeds that of the control greenhouse by 2.6 °C. The relative humidity is found to be 10% lower at night inside the heated greenhouse. This improvement in the microclimate during night has a very positive impact on the quality of fruit and the yield increased by almost 29%.